Penerapan Model Pembelajaran Langsung dalam Meningkatkan Keaktifan dan Hasil Belajar Siswa - Fritfi Mulya Kamara; Muhammad Habib; Gusmaneli . (CV. ITTC INDONESIA, 2026)
This study aims to analyze the application of the Direct Instruction learning model in improving student activeness and learning outcomes. Direct Instruction is a teacher-centered learning model that emphasizes the systematic delivery of knowledge and skills. This research uses a qualitative approach through literature study by reviewing various books, journals, and scientific articles related to Direct Instruction. The results show that the implementation of Direct Instruction can increase student participation in learning activities, improve understanding of concepts, and enhance academic achievement. Effective learning steps and intensive guidance from teachers help students achieve learning objectives optimally. Therefore, Direct Instruction can be used as an alternative learning model to improve the quality of education.